2017
DOI: 10.1002/aic.15889
|View full text |Cite
|
Sign up to set email alerts
|

Formation of liquid–liquid slug flow in a microfluidic T‐junction: Effects of fluid properties and leakage flow

Abstract: Characteristics of liquid-liquid slug flow are investigated in a microchannel with focus on the leakage flow that bypasses droplets through channel gutters. The results show that the leakage flow rate varies in a range of 10.7-53.5% and 8.3-30.9% of the feed flow rate, during the droplet formation (i.e., at T-junction) and downstream flow (i.e., in the main channel), respectively, which highly depends on Ca number and wetting condition. Empirical correlations are proposed to predict them for perfectly and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…13b, the film thickness is still relatively thick in the plane of the longer semi-axis. When the inertia of the aqueous phase increases, the interface might become arcshaped in the plane of the longer semi-axis, with an even larger gap for film flow of the aqueous phase [31]. Such a large aqueous leakage flow around the organic core thread in rectangular and quasi-trapezoidal microchannels of high aspect ratios is very favorable for the persistence of tubing/threading in the cross-junction and annular flow in the downstream channel.…”
Section: Flow Patterns In the Main Microchannelmentioning
confidence: 99%
“…13b, the film thickness is still relatively thick in the plane of the longer semi-axis. When the inertia of the aqueous phase increases, the interface might become arcshaped in the plane of the longer semi-axis, with an even larger gap for film flow of the aqueous phase [31]. Such a large aqueous leakage flow around the organic core thread in rectangular and quasi-trapezoidal microchannels of high aspect ratios is very favorable for the persistence of tubing/threading in the cross-junction and annular flow in the downstream channel.…”
Section: Flow Patterns In the Main Microchannelmentioning
confidence: 99%
“…42 In the same range of Ca Á ϕ, the master curve fitted to own experimental data shows 17 % > Ca Á ϕ > 5% for the emerging droplet. The portion of continuous phase bypassing the droplet is lower by approximately a factor of two for the circular channel tested in this work compared to the rectangular channel tested by Yao et al, 42 The analysis of the effect of capillary number and volume flow rate ratio on the volume of the resulting droplet showed that the final droplet increases with flow rate ratio and decreases with the capillary number. This suggests that the leaking regime as presented by Korczyk et al 18 also applies for the co-flow configuration used in this work.…”
Section: Scanning Protocol and Postprocessingmentioning
confidence: 86%
“…A comparison of data presented by Yao et al 42 to own experimental results revealed that the proportion of continuous phase that bypasses the droplet is approximately reduced by a factor of two, F I G U R E 9 Summary of experimental results in terms ofη = f…”
Section: Scanning Protocol and Postprocessingmentioning
confidence: 91%
See 1 more Smart Citation
“…Polymeric microfluidics have diverse applications that cover a wide area including particle and fluid manipulations. [1][2][3][4][5] Microfluidic paperbased analytical devices (μPADs), at first, were introduced for biological assay. 6 However, recently numerous applications other than biological assay including mixing, fuel cells and cell separation have been introduced for μPADs, [7][8][9] making papers a suitable alternative for polymeric materials.…”
Section: Introductionmentioning
confidence: 99%